Grip-Strength-Lean-Mass Index (GSLMI) as a valuable tool for sarcopenia diagnosis and survival prognosis in cancer patients: a nationwide multicenter cohort study - Zhenyu Huo; Feifei Chong; Siyu Luo; Na Li; Ning Tong; Zongliang Lu; Jing Guo; Ling Zhang; Xin Lin; Mengyuan Zhang; Hongmei Zhang; Muli Shi; et al. (Elsevier, 2025)
Objectives: To identify whether the Grip-Strength-Lean-Mass Index (GSLMI) can precisely diagnose sarcopenia and predict prognosis for cancer patients in clinical settings. Design: A nationwide multicenter cohort study. Setting and participants: 8,831 inpatients aged 18 years and older, histologically diagnosed with cancer and receiving anti-cancer therapy. Measurements: The GSLMI is the ratio of hand grip strength (HGS) divided by lean mass (LM), calculated by the formula: GSLMI = HGS (kg) / LM (kg). Kaplan-Meier curves and Cox models were used to estimate the association between the GSLMI and survival. Results: A total of 3,071 (48.40%) male and 3,274 (51.60%) female patients were enrolled in the study. The prevalence of GLIS-defined sarcopenia was 2,646 (41.70%). The optimal sex-specific thresholds with the best diagnostic performance to identify a low GSLMI were determined to be <0.61 for males and <0.47 for females based on the ROC curves. According to Kaplan-Meier curves, patients with a high GSLMI exhibited better overall survival than those with a low GSLMI (HR = 0.664, 95%CI = 0.604−0.729, log-rank P < 0.001). Multivariable survival analysis revealed that the GSLMI showed an independent association with a lower hazard of death as a continuous variable (HR = 0.70, 95% CI = 0.51−0.96). Conclusions: The GSLMI may serve as a novel diagnostic tool for identifying sarcopenia and may have prognostic value for cancer patients. Using the GSLMI represents a feasible and promising option for better managing the health of patients with cancer.